Antimicrobial activity of sodium hypochlorite, chlorhexidine and MTAD® against Enterococcus faecalis biofilm on human dentin matrix in vitro - Cristiana Francescutti Murad; Luciana Moura Sassone; Monica Cristina Souza; Rivail Antonio Sergio Fidel; Sandra Rivera Fidel; Rafael Hirata Junior (Revista Sul-Brasileira de Odontologia, 2013)
This study evaluated the antimicrobial efficacy of 2.5% and 5.25% NaOCl, 2% gel and liquid CHX and MTAD against Enterococcus faecalis biofilms on human dentin. Material and methods: E. faecalis biofilms grown on dentin matrix of 216 root sections were submerged in test irrigants for 1, 5, 15 and 30 minutes. The antimicrobial activity of the test irrigants were assessed through CFU counts. Biofilm formation over the dentin surface was ensured by SEM analysis. Results: Results showed no statistic difference among CHX gel, 2.5% and 5.25% NaOCl. However, the CHX liquid and MTAD were less effective than 2.5% and 5.25% NaOCl. Only CHX liquid and MTAD had differences in its efficacy depending on the time. Conclusion: The most effective irrigants in eliminating E. faecalis biofilms were 2.5% and 5.25% NaOCl and 2% CHX gel, at all the tested time intervals, in comparison to CHX liquid and MTAD.